EVALUASI PERAN ACCELERATOR STARTUP INDONESIA DALAM MENGEMBANGKAN STARTUP BERORIENTASI KEBERLANJUTAN - Annisa Dwi Rizkadila (Jurnal Akuntansi dan Pajak, 2023)
Accelerator status is a very supportive business program for startup companies in providing educational, mentoring and financial support. The purpose of this study is to obtain in-depth information regarding the evaluation of the role and services of the accelerator program in Indonesia from a startup perspective. Are startups satisfied with the accelerator program, the results of mentoring or coaching and services. This study uses qualitative research methods and focuses on perceptions or opinions of startups regarding the accelerator program and service processes. So this research uses a narrative approach or narrative approach. The types of data used are primary data and secondary data. The research sample was taken using a purposive sampling technique. The data analysis technique uses the 5W +1 H method. This method is used to describe and analyze a given problem by answering 5 components of the questions, namely what, where, when, who, why, and how to each startup. The results of this study reveal that startups can still stand and run their business, but for sustainability orientation some startups reveal that their companies are not sustainability oriented because they have not obtained several factors so they have not achieved the company's main goals. The research results prove that startups are satisfied with the accelerator program in Indonesia. But there are several factors lacking the accelerator program so that the satisfaction level does not reach 100%. This study has indicators of success according to startups as a success factor for the accelerator program Keywords: Start up, Accelerator, and Sustanaibility